NANO CRYPTOCURRENCY AND ITS ARCHITECTURE BASED ON DIRECTED ACYCLIC GRAPHS - DAG - Nogueira, Julio Elias; Sotto, Eder Carlos Salazar (Revista Interface Tecnológica, 2022)
Information technology has brought about important changes and the world has been moved by the digital age. Like many sectors and products, the world has seen the emergence of digital currency as a way to improve internet shopping and sales transactions. Cryptocurrencies appear as an important reality, however, in their creation they presented some errors, which were remedied through improvement, thus the Nano cryptocurrency appeared. The aim of this study is to show the main technical concepts of the Directed Acyclic Graphics (DAG) architecture in cryptocurrency, highlighting the characteristics that make Nano a currency of instant transactions due to its architecture. The article is for Bibliographic Review, with consultations of articles and documents that focus on the subject discussed. The literature points to Nano Cryptocurrency as a digital currency of great potential and with few error rates, a factor of great importance for the virtual market.